2019
DOI: 10.3346/jkms.2019.34.e271
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Intervention on Neurodevelopmental Outcomes in Very Low Birth Weight Infants: a Nationwide Cohort Study in Korea

Abstract: BackgroundTo investigate the incidence of surgical intervention in very low birth weight (VLBW) infants and the impact of surgery on neurodevelopmental outcomes at corrected ages (CAs) of 18–24 months, using data from the Korean Neonatal Network (KNN).MethodsData from 7,885 VLBW infants who were born and registered with the KNN between 2013 to 2016 were analyzed in this study. The incidences of various surgical interventions and related morbidities were analyzed. Long-term neurodevelopmental outcomes at CAs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In our study, the CLABSI group showed a higher proportion of surgical treatment (P=0.006). As a tertiary NICU, the proportion of patients who needed surgical treatment, including pediatric surgery, neurosurgery, cardiothoracic surgery, urologic surgery, and otorhinolaryngologic surgery, was higher (43.3%) than in other Korean NICUs 12) . The reason why surgery is associated with an increased occurrence of CLABSI is unclear.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our study, the CLABSI group showed a higher proportion of surgical treatment (P=0.006). As a tertiary NICU, the proportion of patients who needed surgical treatment, including pediatric surgery, neurosurgery, cardiothoracic surgery, urologic surgery, and otorhinolaryngologic surgery, was higher (43.3%) than in other Korean NICUs 12) . The reason why surgery is associated with an increased occurrence of CLABSI is unclear.…”
Section: Discussionmentioning
confidence: 86%
“…The patients' SNAP-II were categorized as normal (0), mild (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and severe (>40).…”
Section: Methodsmentioning
confidence: 99%
“…Eleven studies were of retrospective design (19,23–32), 19 of prospective design (20–22,33–48). Sample size across studies ranged from 10 to 449 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were of retrospective design (19,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), 19 of prospective design (20)(21)(22)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Sample size across studies ranged from 10 to 449 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is well known that surgical intervention and general anesthesia increase the incidence of neurodevelopmental impairment in preterm infants. Previous studies using national registry data showed that surgery during NICU hospitalization in preterm infants was an independent risk factor for various neurodevelopmental impairments at the age of 2 years or later [39, 40]. Therefore, the question of whether surgery in this early and vulnerable period of life might offset the beneficial fetal neuroprotective effect should be answered.…”
Section: Discussionmentioning
confidence: 99%